2016
DOI: 10.1590/1414-431x20155060
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccines: a controversial issue?

Abstract: Controversy still exists over whether the benefits of the available HPV vaccines outweigh the risks and this has suppressed uptake of the HPV vaccines in comparison to other vaccines. Concerns about HPV vaccine safety have led some physicians, healthcare officials and parents to withhold the recommended vaccination from the target population. The most common reason for not administering the prophylactic HPV vaccines are concerns over adverse effects. The aim of this review is the assessment of peer-reviewed sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
1
24
0
7
Order By: Relevance
“…Among the numerous members of the HPV family, 15 HR-HPV genotypes (types 16,18,31,33,35,39,45,51,52,53,56,58,59, 66 and 68) are etiologically associated with more than 98% of cervical cancers. Effective prophylactic vaccines against the most important carcinogenic HPV types are available, but they do not cover main types of HPV in different countries and regions [7]. Moreover, the prevalence and genotype distribution of HPV substantially vary with ethnicities, demographic and behavioral characteristics, as well as health status [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous members of the HPV family, 15 HR-HPV genotypes (types 16,18,31,33,35,39,45,51,52,53,56,58,59, 66 and 68) are etiologically associated with more than 98% of cervical cancers. Effective prophylactic vaccines against the most important carcinogenic HPV types are available, but they do not cover main types of HPV in different countries and regions [7]. Moreover, the prevalence and genotype distribution of HPV substantially vary with ethnicities, demographic and behavioral characteristics, as well as health status [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The administration of HPV vaccines has been suggested to provide health as well as social benefits, especially in those living in low-resource settings (Nicol et al, 2016). Public HPV vaccination program has been accordingly implemented in numerous developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, it has been shown that the duration of vaccines may last 5-9 years. But more studies are needed about these important issues [35,38]. The development of HPV vaccine is a milestone in the prevention of HPV-related infections and probably in the prevention of cervical cancer.…”
Section: Vaccinesmentioning
confidence: 99%